Children’s Attachment and Relationships with Their Social Environment - Istiqomah Respatiari; Zusy Aryanti; Dwi Enggal Wahyuni (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Children's attachment is a fundamental emotional bond that plays a crucial role in shaping socio-emotional development and children's relationships with their social environment. However, difficulties in social interaction, emotional regulation, empathy, and adaptation remain common among young children and are often associated with the quality of attachment they experience. This study aims to comprehensively examine the relationship between children's attachment and their interactions within family, school, and broader social environments. A Systematic Literature Review (SLR) was conducted following the PRISMA framework by synthesizing peer-reviewed journal articles published between 2022 and 2025. The findings indicate that secure attachment positively influences children's emotional regulation, empathy, self-confidence, communication skills, cooperation, and social adaptation. In contrast, insecure attachment is associated with emotional insecurity, social withdrawal, low self-esteem, and difficulties in establishing healthy interpersonal relationships. The review further highlights that attachment extends beyond parent–child relationships to include teachers and other significant adults who contribute to children's social development. Overall, secure attachment serves as a fundamental foundation for fostering healthy social relationships, emphasizing the importance of collaborative support among families, schools, and communities to promote children's holistic development.